Nxopaxopo wa mapaluxelo ya vafundhisi eka matsalwa ya mbiya ya ntyekanyeka ra B.K.M. Mthobeni na byi n'wi khele Matluka ra Malungana m. - Ngobeni, D. T. (University of Limpopo, 2012)
It introduces the topic of the study, outlining the aims and purpose of the study. It touches on the significance of the study, methodology and literature review. It also contains definitions of the key concepts used in the study. Chapter two focuses on the obituary of the authors of Mibya ya Nyekanyeka and Byi n’wi khele matluka and characterization through Rimmon -Kennan’s methods. Chapter three focuses on the way in which the Vatsonga writers percive the character of pastors as depicted in Mibya ya Nyekanyeka and Byi n’wi khele matluka. Chapter four deals with the theme of each of the following books, namely: Mibya ya Nyekanyeka and Byi n’wi khele matluka. Chapter five. This chapter contains the summary, recommendations and conclusion of the study.
Thesis (M. A.(African Languages)) -- University of Limpopo, 2012
Keywords: Tsonga writers; Character of Pastors; Tsonga literature; African literature - History and criticism